PENERAPAN METODE PEMBELAJARAN STAD (STUDENT TEAM ACHIEVEMENT DIVISION) UNTUK MENINGKATKAN HASIL BELAJAR SISWA MATA PELAJARAN AQIDAH AKHLAK KELAS V MI AL MARHAMAH JABUNG - Rofiqoh Firdausi; Fatkhul Zainudin (Universitas Islam Raden Rahmat Malang, 2022)
The low learning outcomes of students in the subjects of Akidah morality class V Madrasah Ibtidaiyah Al Marhamah Jabung. Many factors that researchers encountered in the learning process that affect activities and learning outcomes such as the lack of teachers in preparing learning methods. To overcome this problem, the researcher applies the STAD type cooperative learning method (student team achievement division) with the hope that student learning outcomes will increase. The formulation of the research problem is: Can the application of the Student Teams-Achievement Divisions (STAD) Cooperative Learning method improve learning outcomes in Aqidah Akhlaq subjects, the subject of Praiseworthy Morals, for fifth grade students of Madrasah Ibtidaiyah Al Marhamah Gunung Kunci Jabung? Meanwhile, the goal is to improve the learning outcomes of fifth graders through the STAD type cooperative learning method (student team achievement division). The subject matter of Akidah Akhlaq is the subject of Praiseworthy Morals for fifth grade students of Madrasah Ibtidaiyah Al Marhamah Gunung Kunci Jabung.